10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Medical students increasingly engage in community-based initiatives to address health inequities among marginalized populations, yet often lack structured guidance for translating intent into feasible practice. This Practice Note describes how the Exploration, Preparation, Implementation, and Sustainment framework was used to guide a student-led foot and wound care initiative serving people experiencing homelessness or housing insecurity in northern Minnesota. In a setting marked by extreme cold and rising homelessness, students partnered with community organizations and volunteer registered nurses to assess needs, develop evidence-informed protocols, and deliver supervised care. Bridging factors, including trusted harm reductionists and clinical supervision, proved critical for aligning outreach with safe clinical practice amid concerns about xylazine-associated wounds from the local drug supply. We illustrate how implementation science can support student-led health promotion by strengthening partnerships, clarifying roles, and enabling adaptation to evolving community needs.